The Capability of Equisetum ramosissium and Typha angustifolia as Phytoremediation Agents to Reduce Nitrate-Phosphate Pollutants and Prevent Microcystis Blooming in Fresh Water Ecosystem - Viky Vidayanti; Catur Retnaningdyah; Soeharjono Soeharjono (Journal of Tropical Life Science, 2012)
The aim of this study is to find out the kind of hydromacrophyte composition having the highest capability to reduce nitrate-phosphate pollutant and Microcystis growth in phytoremediation media using Equisetum ramosissium, Typha angustifolia and the combination of both. Microcystis were obtained from Sutami reservoir, then being inoculated in a media grown by hydromacrophytes (E. ramosissium, T. angustifolia and both of the hydromacrophytes) in the batch culture system. The number of Microcystis was counted every day within fifteen days. Abiotic factors were observe, including the concentration of nitrate using brucine-colorimetry method and orthophosphate (dissolved phosphate) using stannous chloride-colorimetry method on day 0, 6th, 12th and 15th. The growth rate of Microcystis carrying capacity and orthophosphate-nitrate levels among treatments were analysed by ANOVA test. The results showed that E. ramosissium and T. angustifolia in mono and polyculture techniques had similar potentiality to reduce the nitrate and ortophosphate. The concentrations of nitrate and orthophosphate decreased over 70 % in the 6th day after incubation. All of the treatments were able to reduce the carrying capacity of Microcystis up to 46 % , but the growth rates were similar in all media, that is, around 97-170 cells/L/day. Keywords: Equisetum ramosissium, Microcystis, nitrate, phosphate, Typha angustifolia